Silent signals: how N-acyl homoserine lactones drive oral microbial behaviour and health outcomes - Zhao, Zelda Ziyi; Guo, Lifeng; Shan, Wenwen; Chu, Chun Hung; Zhang, Jing (Frontiers in Oral Health, 2024)
BackgroundN-acyl homoserine lactones (AHLs) are small signalling molecules predominantly secreted in Gram-negative bacteria.ObjectiveThe aim is to provide a comprehensive overview of AHLs in oral health.MethodsTwo independent researchers conducted a systematic search of English language publications up to 30 June 2024 in PubMed, Scopus and Web of Science. They screened the title and abstract to retrieve and map out relevant studies on AHLs in oral health, in order to identify key concepts, gaps in knowledge, and areas for further research.ResultsThis study identified 127 articles and included 42 articles. These studies identified AHLs in human oral samples like saliva, dental plaque, tongue swabs, and dentin caries. The studies also found that AHLs regulate cell-to-cell communication of bacteria (quorum sensing) in mature biofilm fostering the production of virulence factors that damage the immune system. AHLs also exert biological effects on human cells and influence oral diseases such as periodontitis and oral squamous carcinoma. Researchers developed AHL inhibitors to interfere with the quorum sensing process and interrupt the communication between bacteria. These inhibitors can be classified into three main categories based on their mechanisms of action to AHLs: AHL synthesis disruptors, AHL competitive inhibitors and AHL enzymatic degraders. These AHL inhibitors can be important tools in the fight against bacterial infections, particularly those caused by Gram-negative bacteria.ConclusionThe literatures indicate that AHLs, as quorum sensing molecules, influence bacterial communication. AHLs have a significant impact in bacterial pathogencity and play a potential role in the pathogenesis of oral diseases. Researchers have developed AHL inhibitors to disrupt bacterial quorum sensing, preventing bacteria from forming biofilms or expressing virulence factors. These studies on AHLs represent a new research direction to develop novel therapeutic strategies to manage oral diseases.